Interleukin-25 Mediates Transcriptional Control of PD-L1 via STAT3 in Multipotent Human Mesenchymal Stromal Cells (hMSCs) to Suppress Th17 Responses - Wang, Wei-Bei (Stem Cell Reports, 2015)
Multipotent human mesenchymal stromal cells (hMSCs) harbor immunomodulatory properties that are therapeutically relevant. One of the most clinically important populations of leukocytes is the interleukin-17A (IL-17A)-secreting T (Th17) lymphocytes. However, mechanisms of hMSC and Th17 cell interactions are incompletely resolved. We found that, along with Th1 responses, hMSCs strongly suppressed Th17 responses and this required both IL-25—also known as IL-17E—as well as programmed death ligand-1 (PD-L1), a potent cell surface ligand for tolerance induction. Knockdown of IL-25 expression in hMSCs abrogated Th17 suppression in vitro and in vivo. However, IL-25 alone was insufficient to significantly suppress Th17 responses, which also required surface PD-L1 expression. Critically, IL-25 upregulated PD-L1 surface expression through the signaling pathways of JNK and STAT3, with STAT3 found to constitutively occupy the proximal region of the PD-L1 promoter. Our findings demonstrate the complexities of hMSC-mediated Th17 suppression, and highlight the IL-25/STAT3/PD-L1 axis as a candidate therapeutic target.